2019
DOI: 10.1136/neurintsurg-2019-015105
|View full text |Cite
|
Sign up to set email alerts
|

MT-DRAGON score for outcome prediction in acute ischemic stroke treated by mechanical thrombectomy within 8 hours

Abstract: ObjectivesThe MRI-DRAGON score includes clinical and MRI parameters and demonstrates a high specificity in predicting 3 month outcome in patients with acute ischemic stroke (AIS) treated with intravenous tissue plasminogen activator (IV tPA). The aim of this study was to adapt this score to mechanical thrombectomy (MT) in a large multicenter cohort.MethodsConsecutive cases of AIS treated by MT between January 2015 and December 2017 from three stroke centers were reviewed (n=1077). We derived the MT-DRAGON scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…However, the association between CBS and 3‐month outcome is mediated by its influence on the reperfusion therapy success, which explains why CBS was no longer an essential factor in our recanalized population [28]. Moreover, the occlusion site appears as a predictive factor in the MT‐DRAGON model because it probably identifies a major subset of severity: tandem occlusion whose treatment is not well codified to date [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the association between CBS and 3‐month outcome is mediated by its influence on the reperfusion therapy success, which explains why CBS was no longer an essential factor in our recanalized population [28]. Moreover, the occlusion site appears as a predictive factor in the MT‐DRAGON model because it probably identifies a major subset of severity: tandem occlusion whose treatment is not well codified to date [14].…”
Section: Discussionmentioning
confidence: 99%
“…A set of observational studies has shown that hypertension, glycemia, fever, ischaemic volume, leptomeningeal collaterals, thrombus characteristics and location are associated with clinically significant optimal reperfusion, regardless of their predictive value and without combining clinical-imaging criteria [12,13]. There is only one recent prediction model, derived from the DRAGON score,in this specific population treated by IVT+MT and who achieves optimal reperfusion [14][15][16][17]. However, it does not explore any predictive factors other than those already composing the primary DRAGON score, thus limiting the understanding of the mechanisms supporting clinically significant optimal reperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Among the common mortality associations in other studies include age 7 10 , 14 , 16 , initial stroke severity 7 9 , 13 16 presenting glucose 8 , 16 , pre-morbid function 7 9 , and history of atrial fibrillation 8 10 , 15 . We similarly found that age, initial stroke severity, presenting glucose, and history of atrial fibrillation were significant univariate associations with mortality risk, though among these factors, the multivariable model demonstrated independent mortality associations with increasing age, presenting NIHSS, and discharge mRS.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical thrombectomy (MT) in acute ischemic stroke substantially improves functional outcome in patients with large vessel occlusion [ 18 , 34 ]. Yet, the time-sensitive selection of patients who will most likely benefit from MT is a critical factor in clinical practice.…”
Section: Introductionmentioning
confidence: 99%